NMR‐based urinary profiling of lactulose/mannitol ratio used to assess the altered intestinal permeability in acute on chronic liver failure (ACLF) patients. (29th September 2016) - Kumar, Dinesh; Pandey, Gaurav; Bansal, Deepak; Rawat, Atul; Kumar, Umesh; Dubey, Durgesh; Guleria, Anupam; Saraswat, Vivek Anand
Abstract: The article presents a simplified NMR‐based protocol for urinary profiling of lactulose/mannitol ratio (LMR) and demonstrates here its utility to assess increased intestinal permeability (IP) in patients with acute on chronic liver failure (ACLF). ACLF is a serious clinical complication associated with chronic liver disease (cirrhosis). The major risk factor in its development is increased IP ('leaky gut'), which has been linked to disease progression and to infectious complications. However, IP has seldom been investigated in patients with ACLF, even though patients frequently report gastrointestinal disorders and associated complications. To this end, we first optimized the NMR‐based targeted profiling of urinary metabolites (i.e. actulose, mannitol, and creatinine) and subsequently used this resulted protocol (a) first to evaluate the altered IP in ACLF patients and then (b) to explore its utility for monitoring the treatment response in these patients. The normal profiles were obtained for 7 age and sex matched healthy volunteers. The results revealed that the urinary LMR excretion was significantly higher in ACLF patients compared to normal controls (median 0.7, range (0.12–2.84), vs median 0.11, range (0.02–0.28), p < 0.001) suggesting that the ACLF patients' exhibit altered IP. However, the LMR excretion in six clinically improved follow‐up ACLF patients was comparable to normal controls indicating restored IP after the treatment. The protocol—as demonstrated here with ACLF—is equally applicable for evaluating IP or mucosal barrier function in other intestinal disorders with reasonable sensitivity and specificity, highlighting its general utility. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Assessment of intestinal permeability (IP) is crucial for evaluation of abnormal mucosal barrier function, thus may aid early treatment and predict prognosis. It also correlates well with biopsy/endoscopy results. NMR‐based urinary profiling of lactulose/mannitol ratio has been demonstrated here to assess the increased IP in acute on chronic liver failure (ACLF) patients and its amelioration after the treatment.